Theoretical and Experimental Understanding of the Anomalous Odd-to-Even Isotope Ratios of Tin in a 1 + 1 Single-Colour Resonance Ionization Mass Spectrometry: Revisited - Manda Sankari (International Journal of Optics)
Differences in the odd to even response for tin isotopes has been observed earlier in resonance ionization experiments, resulting in anomalous odd to even isotope ratios. I have used a theoretical approach known as the spectral simulation approach to understand the cause for such anomaly and the anomaly has also been experimentally verified and found to be in good agreement. The effects of laser parameters such as intensity, accuracy of the excitation laser wavelength and bandwidth on the determination of the tin isotope ratio have been analyzed theoretically and experimentally. The source for such anomalies was found to be the inaccuracy in the excitation laser wavelength. For the 5p2 (3P0) − 5p 6s (3P01) (286.3317 nm) transition, an inaccuracy of the order of 𝛾𝐿 in the peak frequency of the excitation laser (𝛾𝐿=15 GHz) can cause anomalies as large as ∼31% (𝛽=0.31). Use of a very large bandwidth laser (∼60 GHz) reduces the anomaly to as small as −0.003. Alternatively by employing a relatively narrow band laser (∼1.2 GHz), it has been observed that inaccuracy of the order of 3-4 𝛾𝐿 in the laser peak frequency does not induce anomalies >0.05. The isotope ratio is sensitive to the inaccuracy in the excitation laser wavelength for an intermediate linewidth laser.